Review of Legal Protection Against Sexual Violence by Doctors Based on the Law on Medical Practice - Ismail, Muhammad Reza; Rahayu, Sri Dewi; Asamara, Teddy; Sanusi, Sanusi (Journal of Legal and Cultural Analytics, 2025)
Sexual violence by doctors is a serious violation of human rights that can have profound psychological and social impacts on victims. Based on Law Number 29 of 2004 concerning Medical Practice, doctors should carry out their profession under applicable medical standards and codes of ethics. Article 51 regulates the obligation of doctors to provide medical services under standards, while Article 79 provides criminal sanctions for doctors who deliberately do not fulfill their administrative and professional commitments. This study uses a normative juridical approach to analyze the legal provisions that protect victims of sexual violence in medical practice, focusing on Article 51 and Article 79 of the Medical Practice Law. The primary sources of data are laws and regulations and related legal literature. The study results show that the effectiveness of legal protection depends on consistent implementation and enforcement of the law and synergy between the law and medical professional institutions. In addition, preventive aspects such as ethical education and transparent oversight mechanisms in medical institutions are essential. Psychological and social assistance for victims is also an integral part of the protection system. With a holistic approach involving the law, professional ethics, and victim protection, it is hoped that it can create a safe and dignified health environment. Evaluation and development of legal policies and professional ethics are needed to strengthen legal protection for victims of sexual violence in medical practice in Indonesia.